Fiqih Muamalah Financial Technology - Julita Julita; Andri Soemitra (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The current research will classify the research topics of fiqh muamalah financial technology to find out the existing research map so that it can be seen what has been researched and further research opportunities for the expansion of research and development of muamalah fiqh. By using qualitative research with content analysis and focus discussion groups with economists, the articles used were 25 articles published in journals in Indonesia from 2017 to 20212. The topic of this muamalah fiqh research consists of 4 topics, namely (1) Development of Fintech, (2) Fintech dynamics, (3) Financial Technology Concepts, (4) Financial technology in terms of sharia economic perspective.